Impact of older age on local treatment decisionss - (:unkn) unknown (Churchill Livingstone, 2019)
Managing elderly breast cancer patients brings challenges both to physicians and patients themselves. There are certain controversial issues regarding local treatment of early breast cancer in this population. Since elderly patients are more likely to have comorbidities and functional limitations, they are more prone to undertreatment. Although surgical treatment in elderly patients were reported to be safe, severity and number of comorbidities are shown to be related with increased complications, hence may lead to higher mortality and lower life quality. Therefore, frailty is one of the concerns which prevents elderly patients to receive standard-of-care local treatment. Nevertheless, breast cancers developing in elderly are more likely to be low grade and luminal type. Until now, primary endocrine treatment without surgical resection, omitting whole breast irradiation after partial mastectomy and avoiding sentinel lymph node biopsy, which are otherwise accepted as standard-of-care, were questionned in healthy, low-risk, elderly fit patients. Two main issues were suggested to be considered when assessing the impact of local treatment options in this patient group; the clinical significance of treatments’ effects, and the patients’ expectations. Due to their vulnerability, baseline geriatric assessment should be the initial step for management in elderly breast cancer patients. Even in those who are healthy and fit with long life-expectancy, de-escalation in management might be an option in low-risk patients after considering patients’ individual expectations and limited clinical benefits of standard local treatment options. © 2019 Elsevier Ltd.
Keywords: Breast cancer; Elderly; Local treatment; Primary endocrine treatment; Sentinel lymph node biopsy; Whole breast irradiation